1960
DOI: 10.1139/o60-053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Dietary Lysine Deficiency on the Concentration of Amino Acids in the Deproteinized Blood Plasma of Chicks

Abstract: A lysine-deficient basal diet, both with and without supplemental lysine added, was fed to groups of Barred Plymouth Rock cockerels from hatching to 4 weeks of age. At this time blood samples were taken from the carotid artery and pooled for each group. Twelve amino acids were determined in the deproteinized plasma by microbiological assay. Deproteinized plasma from birds receiving the lysine-deficient diet was lower in lysine content and higher in threonine and tyrosine than that from birds fed the lysine-sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1962
1962
1996
1996

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Gray et al (1960), Morrison et al (1961) and Long (1966) have observed a significant decrease in plasma lysine as plasma threonine increased. In this experiment, the increase in plasma threonine as dietary threonine was increased resulted in a linear (P<.01) and quadratic (P<.005) decrease in fasted plasma lysine.…”
Section: Death Lossmentioning
confidence: 97%
“…Gray et al (1960), Morrison et al (1961) and Long (1966) have observed a significant decrease in plasma lysine as plasma threonine increased. In this experiment, the increase in plasma threonine as dietary threonine was increased resulted in a linear (P<.01) and quadratic (P<.005) decrease in fasted plasma lysine.…”
Section: Death Lossmentioning
confidence: 97%
“…These phenomena have been recognized by several workers. 26 -30) Gray et al 28 ) and Morrison et al 29 ) reported that the chicks given a lysine-deficient diet had lower levels of free lysine and higher levels of free threonine in the plasma than those given a diet containing adequate amounts of lysine.…”
mentioning
confidence: 99%
“…The former effect might be explained by the continuation of the fasting effect as amino acids have been observed to decrease in concentration with time in chicks upon fasting (Gray et al, 1960;Hill and Olsen, 1963b). However, two hours after ingesting a protein meal, the digestive processes are operating at a high intensity.…”
Section: Discussionmentioning
confidence: 99%